The impact of pre-transplant ventricular assist device support in pediatric patients with end-stage heart failure on the outcomes of heart transplantation—“a single center experience” - L. Lily Rosenthal; L. Lily Rosenthal; L. Lily Rosenthal; Carola Grinninger; Sarah Marie Ulrich; Robert Dalla Pozza; Nikolaus A. Haas; Paolo Brenner; Michael Schmoeckel; Sebastian Michel; Sebastian Michel; Sebastian Michel; et al. (Frontiers in Cardiovascular Medicine)
IntroductionThe objective of this study was to examine the impact of ventricular assist device support as a bridge to heart transplantation in children with end-stage heart failure. In light of the limited availability of donor organs, particularly in Europe, the number of children requiring ventricular assist device support is rising at an unavoidable rate.MethodsWe performed a retrospective cohort study of patients who underwent a single and primary pediatric heart transplantation. Patients were divided into two groups: with pre transplant ventricular assist device (VAD) support and without VAD support. The primary outcome was survival at the follow-up evaluation. The time point designated as “time 0” was defined as the time of heart transplantation. Secondary outcome was examined by mean of univariable and multivariable logistic regression, severity of cardiac disease based on ECMO-support pre VAD-support, mean waiting time for transplantation, mean OR time and mean length of hospital stay before and after transplantation.Results144 patients could be included in the final analysis. The cumulative survival rate at follow-up period was 67 ± 10% in group 1 vs. 60 ± 6% in group 2 (P = 0.769). The mean waiting time (days) on the list was 205 ± 155 in group 1 and 119 ± 69 in group 2 (P = 0.002). The mean length of hospital stay (days) was 214 ± 209 in group 1 and 128 ± 91 days in group 2. Early primary-graft-failure was 10% in group 1 and 13% in group 2. Odds ratio [OR] is as follows: 1.992, 95% confidence interval [CI]: 0.983–1.007, p = 0.266, aortic clamp time per minutes: OR: 1.008, 95% CI: (0.997–1.019), p = 0.164, HLM time per minutes: OR: 0.996, 95% CI: (0.991–1.001), p = 0.146, Operation time per minutes: OR: 1.000, 95% CI: (0.995–1.004), p = 0.861.ConclusionThe provision of pre-HTx VAD support does not have an adverse effect on the short- and long-term survival of pediatric patients undergoing HTx. A higher mortality rate was observed among children under three months of age with congenital heart disease. The patients who received VAD support were in a critical condition and required more ECMO support. The results demonstrated a statistically significant correlation between prolonged waiting times and length of hospital stay in group 1. More homogeneous and adequately powered cohorts are needed to better understand the impact of VAD support on posttransplant outcomes.